Termites and Rhizoctonia sp.: major problems in robusta coffee cuttings cultivated on different planting media - Susilawati, Susilawati; Sari, Mahardika Puspita; Firdaus, Nur Kholis; Pranowo, Dibyo (Universitas Lampung, 2023)
Robusta coffee is one of the plantation commodities vegetative propagated through cuttings to keep them in the same characteristics as their parents. The main problems in cuttings propagation are pests and diseases are cause damage to the planted cuttings. This research aimed to study the causal agent and its damage to robusta coffee cuttings planted on different media. The research was conducted from September 2020 to March 2021 in the experimental field station (KP) Pakuwon and the Integrated Laboratory of Balittri. The arrangement of the experimental design was a split plot with two repetitions. The main plot was the type of media planted consisting of sand, sand + fertilizer (1: 1), sand + soil (1: 1), soil + fertilizer (1: 1), sand + soil + fertilizer (1: 1: 1). The subplot was a Robusta coffee clone consisting of BP308, BP393, and SA203. The results showed that the highest percentage of damage caused by termites and Rhizoctonia sp. was observed on the cuttings planted on sand + fertilizer mixture media while the lowest was on sand media. The termites found in the robusta coffee cuttings were Macrotermes gilvus.